Situating Health Within the 2030 Agenda-A Practical Application of the Sustainable Development Goals Synergies Approach - Daniel Helldén; Nina Weitz; Måns Nilsson; Måns Nilsson; Tobias Alfvén; Tobias Alfvén (Frontiers Media S.A., 2022)
Background: The Sustainable Development Goals (SDGs) are integrated, indivisible and interdependent and interact and affect each other directly and indirectly. However, the 2030 Agenda does not attempt to identify or characterise these interactions.Evidence: The SDG Synergies approach was developed to enable the investigation of the strength and nature of interactions between SDGs based on the perception of a multistakeholder group. Two examples are given to concretely demonstrate how this approach overcomes present challenges and can be applied to situate health within the 2030 Agenda.Policy Options and Recommendations: There are clear benefits to situate desired health policy outcomes within the 2030 Agenda, and the SDG Synergies approach can be used as lever for including health aspects in traditional non-health sectors. Although focusing on specific health policies cannot be substituted with multisectoral policies alone, utilizing tools and methods such as the SDG Synergies approach can help policy makers put health at the centre of the SDGs.Conclusion: SDG Synergies is an impactful approach for policy makers to gain a systemic understanding of how broader sustainable development shape the health and well-being of people and vice versa.